Evaluation of Bone Insertion Level of Support Teeth in Class I Mandibular Removable Partial Denture Associated With an Osseointegrated Implant: A Study Using Finite Element Analysis - Verri, Fellippo Ramos [UNESP]; Pellizzer, Eduardo Piza [UNESP]; Pereira, João Antonio [UNESP]; Zuim, Paulo Renato Junqueira [UNESP]; Santiago Júnior, Joel Ferreira [UNESP] (Lippincott Williams & Wilkins, 2011)
Purpose: This study evaluated the influence of distal extension removable partial denture associated with implant in cases of different bone level of abutment tooth, using 2D finite element analysis.Materials and Methods: Eight hemiarch models were simulated: model A-presenting tooth 33 and distal extension removable partial denture replacing others teeth, using distal rest connection and no bone lost; model B-similar to model A but presenting distal guide plate connection; model C-similar to model A but presenting osseointegrated implant with ERA retention system associated under prosthetic base; model D-similar to model B but presenting osseointegrated implant as described in model C; models E, F, G, and H were similar to models A, B, C, and D but presenting reduced periodontal support around tooth 33. Using ANSYS 9.0 software, the models were loaded vertically with 50 N on each cusp tip. For results, von Mises Stress Maps were plotted.Results: Maximum stress value was encountered in model G (201.023 MPa). Stress distribution was concentrated on implant and retention system. The implant/removable partial denture association decreases stress levels on alveolar mucosa for all models.Conclusions: Use of implant and ERA system decreased stress concentrations on supporting structures in all models. Use of distal guide plate decreased stress levels on abutment tooth and cortical and trabecular bone. Tooth apex of models with reduced periodontal support presented increased stress when using distal rest. (Implant Dent 2011;20:192-201)
Keywords: biomechanics; finite element analysis; removable partial denture; dental implant; dental stress analysis